Distance to human populations influences epidemiology of respiratory disease in desert tortoises. Issue 1 (9th December 2014) - Berry, Kristin H.; Coble, Ashley A.; Yee, Julie L.; Mack, Jeremy S.; Perry, William M.; Anderson, Kemp M.; Brown, Mary B.
Abstract We explored variables likely to affect health of Agassiz's desert tortoises (Gopherus agassizii) in a 1, 183‐km2 study area in the central Mojave Desert of California between 2005 and 2008. We evaluated 1, 004 tortoises for prevalence and spatial distribution of 2 pathogens, Mycoplasma agassizii and M. testudineum, that cause upper respiratory tract disease. We defined tortoises as test‐positive if they were positive by culture and/or DNA identification or positive or suspect for specific antibody for either of the two pathogens. We used covariates of habitat (vegetation, elevation, slope, and aspect), tortoise size and sex, distance from another test‐positive tortoise, and anthropogenic variables (distances to roads, agricultural areas, playas, urban areas, and centroids of human‐populated census blocks). We used both logistic regression models and regression trees to evaluate the 2 species of Mycoplasma separately. The prevalence of test‐positive tortoises was low: 1.49% (15/1, 004) for M. agassizii and 2.89% (29/1, 004) for M. testudineum. The spatial distributions of test‐positive tortoises for the 2 Mycoplasma species showed little overlap; only 2 tortoises were test‐positive for both diseases. However, the spatial distributions did not differ statistically between the 2 species. We consistently found higher prevalence of test‐positive tortoises with shorter distances to centroids of human‐populated census blocks. The relationship between distance to human‐populated census blocks and tortoises that are test‐positive for M. agassizii and potentially M. testudineum may be related to release or escape of captive tortoises because the prevalence of M. agassizii in captive tortoises is high. Our findings have application to other species of chelonians where both domestic captive and wild populations exist. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.